When Wrestling Is the Bootstrap (and Basketball, Too): Commentary on Andrew Eig's "Self-Defeating Aggression and the Need for Rough-and-Tumble Play in Adult Analysis". Issue 3 (2nd September 2022) - Kaufmann, Peter
Abstract : This discussion of Andrew Eig's "Self-Defeating Aggression and the Need for Rough and Tumble Play in Adult Analysis" (playfully) focuses on the clinical process that occurs between Eig and his patient, both appreciating how Eig contains Ezra's aggression and highlighting how he fosters Ezra's sense of capability. It also expands Eig's explicit theory of therapeutic action in the case, bringing in Mitchell's ideas about bootstrapping and repetitive enactment or impasse, as well as Kohut's and Winnicott's ideas about the possible developmental and adaptive aspects of aggressive states. Finally, it builds on Eig's implication that shared aggression can be a vitalizing feature in treatment by introducing the concept of joining with the patient's aggression, using basketball as a metaphor for this joining.